2015
DOI: 10.1113/jphysiol.2014.288381
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cortical lateralization during olfactory discrimination learning

Abstract: Bilateral cortical circuits are not necessarily symmetrical. Asymmetry, or cerebral lateralization, allows functional specialization of bilateral brain regions and has been described in humans for such diverse functions as perception, memory and emotion. There is also evidence for asymmetry in the human olfactory system, although evidence in non-human animal models is lacking. In the present study, we took advantage of the known changes in olfactory cortical local field potentials that occur over the course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 74 publications
(160 reference statements)
10
40
0
Order By: Relevance
“…Our study showed that although SWDs were not lateralized to the left or right hemisphere, myoclonic seizures exhibited a greater fraction of spikes starting in the right S1 than the left. Our finding of myoclonic seizure lateralization onset to right S1 in Gabra1 +/A322D mice is consistent with previous reports showing EEG lateralization in human JME, rodent audiogenic seizures, and rodent sensory processing …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study showed that although SWDs were not lateralized to the left or right hemisphere, myoclonic seizures exhibited a greater fraction of spikes starting in the right S1 than the left. Our finding of myoclonic seizure lateralization onset to right S1 in Gabra1 +/A322D mice is consistent with previous reports showing EEG lateralization in human JME, rodent audiogenic seizures, and rodent sensory processing …”
Section: Discussionsupporting
confidence: 93%
“…Our finding of myoclonic seizure lateralization onset to right S1 in Gabra1 +/A322D mice is consistent with previous reports showing EEG lateralization in human JME, 27 rodent audiogenic seizures, 28,29 and rodent sensory processing. [30][31][32] In addition, we found that myoclonic seizures initiate more focally within the sensorimotor cortex than SWDs. The majority of spikes in myoclonic seizures were initially detected exclusively in S1 electrodes, whereas a substantial fraction of SWD spikes were detected in S1 electrodes and at least one M1 electrode.…”
Section: Differential Activation Of the Thalamocortical Network In Swmentioning
confidence: 64%
“…Perhaps reflecting the importance of these brain regions for regulating maternal behaviour, such as recognition of pup vocalisations & scents (Cohen et al, 2015;Richter et al, 2005), gender differences in oxytocin receptor expression have been reported. For example, denser receptor expression was found in the piriform cortex in female compared to male mice .…”
Section: Oxytocin Enhances the Salience Of Socially Relevant Sensorymentioning
confidence: 99%
“…Rats/Long Evans males anterior PC LEFT Enhanced beta frequency band oscillations during the first stages of odour discrimination learning Performance-and context-dependent asymmetry [16] Rats/Long Evans males anterior PC orbitofrontal cortex…”
Section: Species/strain/sex Brain Structure Side Measure Referencementioning
confidence: 99%
“…When considering olfactory learning, a study in rats has shown a highly significant lateralisation of translocation of enzyme protein kinase C from the cytosol to the membrane in the left PC [15]. More recently, Cohen and colleagues [16] showed a transient interhemispheric asymmetry in the anterior PC oscillatory activity at the initial stages of an odour discrimination task. This asymmetry was mainly the result of an enhanced event-related oscillatory activity in the left than in the right anterior PC.…”
mentioning
confidence: 99%